Cellular and Humoral SARS-CoV-2 Vaccination Responses in 192 Adult Recipients of Allogeneic Hematopoietic Cell Transplantation - Thomas Meyer; Gabriele Ihorst; Ingrid Bartsch; Robert Zeiser; Ralph Wäsch; Hartmut Bertz; Jürgen Finke; Daniela Huzly; Claudia Wehr (Vaccines, 2022)
To determine factors influencing the vaccination response against SARS-CoV-2 is of importance in recipients of allogeneic hematopoietic cell transplantation (allo-HCT) as they display an increased mortality after SARS-CoV-2 infection, an increased risk of extended viral persistence and reduced vaccination response. Real-life data on anti-SARS-CoV-2-S1-IgG titers (n = 192) and IFN-γ release (n = 110) of allo-HCT recipients were obtained using commercially available, validated assays after vaccination with either mRNA (Comirnaty™, Pfizer-BioNTech™, NY, US and Mainz, Germany or Spikevax™, Moderna™, Cambridge, Massachusetts, US) or vector-based vaccines (Vaxzevria™,AstraZeneca™, Cambridge, UK or Janssen COVID-19 vaccine™Johnson/Johnson, New Brunswick, New Jersey, US), or after a heterologous protocol (vector/mRNA). Humoral response (78% response rate) was influenced by age, time after transplantation, the usage of antithymocyte globulin (ATG) and ongoing immunosuppression, specifically corticosteroids. High counts of B cells during the vaccination period correlated with a humoral response. Only half (55%) of participants showed a cellular vaccination response. It depended on age, time after transplantation, ongoing immunosuppression with ciclosporin A, chronic graft-versus-host disease (cGvHD) and vaccination type, with vector-based protocols favoring a response. Cellular response failure correlated with a higher CD8+ count and activated/HLA-DR+ T cells one year after transplantation. Our data provide the basis to assess both humoral and cellular responses after SARS-CoV2 vaccination in daily practice, thereby opening up the possibility to identify patients at risk.